THE USE OF BINARY OPTIMIZATION AND HYDROLOGIC MODELS TO FORM RIPARIAN BUFFERS - Cerucci, Marcelo; Conrad, Jon M. (Journal of the American Water Resources Association, 2003)
Riparian buffers are considered important management options for protecting water quality. Land costs and buffer performance, which are functions of local environmental characteristics, are likely to be key attributes in the selection process, especially when budgets are limited. In this article we demonstrate how a framework involving hydrologic models and binary optimization can be used to find the optimal buffer subject to a budget constraint. Two hydrologic models, SWAT and REMM, were used to predict the loads from different source areas with and without riparian buffers. These loads provided inputs for a binary optimization model to select the most cost efficient parcels to form a riparian buffer. This methodology was applied in a watershed in Delaware County, New York. The models were parameterized using readily available digital databases and were later compared against observed flow and water quality data available for the site. As a result of the application of this method, the marginal utility of incremental increases in buffer widths along the stream channel and the set of parcels to form the best affordable riparian buffer were obtained.